Periodic focal epileptiform discharges. Issue 8 (August 2019) - Tatum, William O.; Feyissa, Anteneh M.; ReFaey, Karim; Grewal, Sanjeet S.; Alvi, Mohammed A.; Castro-Apolo, Ramiro; Roth, Grayson; Segura-Duran, Ivan; Mahato, Deependra; Ruiz-Garcia, Henry; Pamias-Portalatin, Eva; Yelvington, Kirsten; et al.
Highlights: Periodic Focal Epileptiform Discharges (PFEDs) are a novel epileptiform pattern identified using HD-ECoG. PFEDs have a temporospatial scale distinct from other epileptiform discharges on ECoG. No relationship to seizures was identifiable in our cohort with brain tumor and seizures. Abstract: Objective: To report intraoperative periodic focal epileptiform discharges (PFEDs) during awake craniotomy using high-density electrocorticography (HD-ECoG). Methods: We retrospectively analyzed 81 patients undergoing awake craniotomy between 9/29/2016 and 7/5/2018. Intraoperative HD-ECoG was performed with direct electrocortical stimulation (DECS) for functional brain mapping. Real-time interpretation was performed and compared to scalp EEG when performed. Perioperative seizures, surgical complications, and characteristics of PFEDs were assessed. Results: 69/81 patients (mean age 48.5 years) underwent awake surgery; 55 operated for brain tumor, 11 for epilepsy and 3 for cavernomas. A focal abnormality on brain MRI was present in 63/69 (91.3%) patients. 43/69 (62.3%) patients had seizures preoperatively, 4/69 (5.7%) had seizures during DECS. PFEDs were identified in 11 patients (15.9%); 2 on depth recording and 9 during intraoperative HD-ECoG. 32 patients (46.3%) had preoperative EEG. HD-ECoG detected more epileptiform discharges (EDs) than standard EEG (32/43; 74.4% vs 9/32; 28.1%) ( p = <0.001 ). Of 9/43 patients with PFEDs on HD-ECoG, 7 patients also had scalp EEG but only one case had EDs (p = 0.02), and 0/32 had periodic EDs. Conclusions: Intraoperative PFEDs are novel, highly focal EDs approximating a single gyrus. In patients with brain tumors, PFEDs did not demonstrate a relationship to pre-operative seizures though has similarities to other common waveforms in patients with epilepsy. Significance: PFEDs expand our understanding of the interictal-ictal continuum and highlight improved temporo-spatial information obtained from increasing sensor density during intracranial EEG recording.